Efektivitas Program Pojok Literasi Ku Sebagai Media Dalam Meningkatkan Literasi Masyarakat di Desa Bumi Sari - santoni saputra; Nurhaslita Sari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
This study discusses the effectiveness of the Ku Literacy Corner Program in Bumi Sari Village, Beutong District, Nagan Raya Regency, the method used in this case is a qualitative research method that emphasizes the descriptive method, while the purpose of the Ku Literacy Corner Program is as a learning platform that can provide learning which is still unknown in the midst of the people of Bumi Sari Village, from the results obtained when my Literacy Corner Program was running, there was a development of insights that were obtained by the surrounding community and became a new science that was obtained, my literacy corner program has 5 corners, namely: writing corner , a reading corner, an introduction to the internet corner, a Microsoft Office corner and a computer operation corner. In connection with the implementation of this program, there have been many changes in mindset and in active literacy for the people in Bumi Sari Village, Beutong District, Nagan Raya Regency, progressing.